Etos Kerja Berbasis Agama dan Budaya Pada Komunitas Pedagang Pidie (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study aims to examine how Islamic teachings and local Pidie cultural traditions shape the work ethic of merchants and to clarify the mechanisms that connect religious motivation with culturally embedded practices. A phenomenological approach was used through in-depth interviews, participant observation, and document analysis. The informants consisted of merchants of various scales who have longstanding experience in the trading sector. The findings show that the work ethic of Pidie merchants emerges from the integration of Islamic values that encourage honesty, discipline, and responsibility with cultural values that emphasize hard work, independence, social honor, and the tradition of migration. These two sets of values interact as a unified mechanism that strengthens diligence, integrity, and economic resilience. The study concludes that the work ethic of Pidie merchants is grounded not only in religious teachings but also in cultural values that are lived and transmitted within the community. The integration of these values generates a resilient and productive pattern of work that is closely linked to social honor and moral responsibility. The findings affirm that the work ethic of Muslim communities should be understood as the result of a continuous interaction between religious belief and cultural experience within daily economic life. Abstrak: Penelitian ini bertujuan memahami bagaimana nilai Islam dan budaya lokal Pidie membentuk pola etos kerja pedagang serta menjelaskan mekanisme yang menghubungkan motivasi religius dengan praktik budaya yang terinternalisasi. Penelitian ini menggunakan pendekatan fenomenologis dengan teknik wawancara mendalam, observasi partisipatif, dan analisis dokumen. Informan terdiri dari pedagang berskala besar, menengah, dan kecil yang telah lama berpengalaman dalam dunia perdagangan. Hasil penelitian menunjukkan bahwa etos kerja pedagang Pidie muncul dari perpaduan nilai Islam yang mendorong kejujuran, disiplin, dan tanggung jawab dengan nilai budaya yang menekankan kerja keras, kemandirian, kehormatan sosial, dan tradisi merantau. Keduanya membentuk satu mekanisme yang bekerja bersamaan dalam membangun ketekunan, integritas, dan daya saing ekonomi. Penelitian ini menyimpulkan bahwa etos kerja pedagang Pidie tidak hanya berakar pada ajaran agama tetapi juga pada nilai budaya yang hidup dan diwariskan dalam komunitas. Integrasi keduanya menciptakan pola kerja yang tangguh, produktif, dan berorientasi pada kehormatan sosial serta tanggung jawab moral. Temuan ini menegaskan bahwa etos kerja masyarakat Muslim perlu dipahami sebagai hasil dari interaksi berkelanjutan antara keyakinan religius dan pengalaman budaya dalam kehidupan ekonomi sehari-hari.
Keywords: Etos kerja; Nilai agama; Budaya lokal; Komunitas pedagang; Pidie